MicroRNA-200c Mitigates Invasiveness and Restores Sensitivity to Microtubule-Targeting Chemotherapeutic Agents - Cochrane, Dawn R. (Mol Cancer Ther, 2009)
The transcription factor ZEB1 is normally not expressed in epithelial cells. When inappropriately expressed in carcinomas, ZEB1 initiates epithelial to mesenchymal transition due to its ability to repress E-cadherin and other genes involved in polarity. Recently, ZEB1 and ZEB2 have been identified as direct targets of the microRNA-200c family. We find that miR-200c levels are high in well-differentiated endometrial, breast and ovarian cancer cell lines, but extremely low in poorly-differentiated cancer cells. Low or absent miR-200c results in aberrant expression of ZEB1 and consequent repression of E-cadherin. Reinstatement of miR-200c to such cells restores E-cadherin and dramatically reduces migration and invasion. Microarray profiling reveals that in addition to ZEB1 and ZEB2, other mesenchymal genes (such as FN1, NTRK2, and QKI), which are also predicted direct targets of miR-200c, are indeed inhibited by addition of exogenous miR-200c. One such gene, class IIIβ-tubulin (TUBB3), which encodes a tubulin isotype normally found only in neuronal cells, is a direct target of miR-200c. This finding is of particular significance because we show that restoration of miR-200c increases sensitivity to microtubule-targeting agents by up to 85%. Since expression of TUBB3 is a common mechanism of resistance to microtubule-binding chemotherapeutic agents in many types of solid tumors, the ability of miR-200c to restore chemosensitivity to such agents may be explained by its ability to reduce TUBB3. Because miR-200c is crucial for maintenance of epithelial identity, behavior, and sensitivity to chemotherapy, we propose that it warrants further investigation as a therapeutic strategy for aggressive, drug-resistant cancers.